Production testing of the winter rape (Brassica napus L.) - Ф. М. Парій; А. І. Опалко; А. Д. Черненко (Plant Varieties Studying and Protection)
Advantages of heterotic hybrids of the winter rape in the competitive and in the production testing proven. While certain advantages in the productivity of cultivar of the Czech selection of Odila above the domestic cultivar of Dangal got in the competitive testing in the production testing confirmed. It is established that the greatest productivity in the production testing was had hybrids Vsesvit F1t Zapalnyj Fb G-3 Fi and G-4 Fi, which are characterized the stable and yearly high productivity and combine the productivity with adaptability to the environmental conditions of area of Forest- steppe of Ukraine.